The beach flies of the Mascarene Islands (Diptera: Canacidae: Tethininae) - Munari, Lorenzo; Kirk-Spriggs, Ashley H.; Mcgregor, Gillian K. (Zootaxa, 2020)
An intertidal survey of 34 sampling stations on the main Mascarene Islands of La Réunion, Mauritius and Rodrigues, was conducted between 2015 and 2018. Results of the survey revealed five species of Tethininae, viz. Afrotethina aurisetulosa (Lamb), Dasyrhicnoessa ferruginea (Lamb), D. insularis (Aldrich), D. vockerothi Hardy & Delfinado and Pseudorhicnoessa rattii Munari, all of which are new to one or more of the Mascarenes (A. aurisetulosa, D. ferruginea and D. insularis new to all three islands; D. vockerothi new to Mauritius and Rodrigues; and P. rattii new to Rodrigues). Sampled species exhibit a very close affinity with those that occur on Seychelles and the composition of the two faunas is notably superimposable. The distributions of the five species on the three main islands is mapped and an identification key to all genera and species of both archipelagos is provided, with the most significant diagnostic features illustrated. The survey also revealed that the rather common Afrotropical genus Horaismoptera Hendel, which is represented in East Africa, Madagascar, and the southern Arabian Peninsula by H. vulpina Hendel, is most likely absent from both archipelagos.